Why geographic dispersion before its time: Industrial policy and economic geography in the People's Republic of China - Yiyun Wu; Xiwei Zhu (Asian Development Bank Institute (ADBI), 2017)
This paper investigates the trends and determinants of geographic concentration and industrial specialization in the People's Republic of China (PRC) using interprovincial panel data for the period from 1999 to 2010. It shows that, after 2005, both geographic concentration and industrial specialization began to decrease, resulting in an increased similarity of provincial industrial structure. Industrial policies of provincial governments cause geographic dispersion and inverse specialization. The result is robust when using instrumental variables to deal with possible reverse causality and omitted variable problems. The mechanism behind this is that central government industrial policy, which tends to last for several years, is an important reference document for each provincial planner. This causes the less-developed regions to deviate from their comparative advantages, resulting in a combination of insufficient geographic concentration and inverse specialization in the PRC.
Keywords: L59; L60; R12; 330; geographic concentration; dispersal; industrial policy; specialization; local government; provincial government; economic geography